Physical activity level and sedentary behavior among students - Diego Augusto Santos Silva; Jadson de Oliveira Lima; Roberto Jerônimo dos Santos Silva; Rosa Luciana Prado (Universidade Federal de Santa Catarina, 2009)
The objective of this study was to determine the physical activity level (PAL) and sedentary behavior of students from the city of Aracaju (SE). A total of 1028 students of both genders participated in the study, with a mean age of 15.38 (2.44) years for girls and 15.24 (2.40) years for boys. Among the sample, 24.7% were children and 75.3% were adolescents, with a mean age of 12.07 (0.88) and 16.39 (1.72) years, respectively. An instrument already used in Brazilian studies was applied to identify the average time (hours) watching TV per day (hTV) and PAL - PAQ-C. Descriptive statistics, t-test for independent samples, Fisher's exact test and comparison test between two proportions were used for data analysis, with the level of significance set at 5% (p≤0.05). Boys presented a significantly higher physical activity score 2.25 (0.60) than girls. The prevalence of sedentarism was 72.5, 89.3 and 85.2% in the groups of children and adolescents and in the group as a whole, respectively, for girls, and 55.4, 74.8 and 69.8% for boys. No differences in hTV were observed between genders or between sedentary and physically active students (p > 0.05). We conclude that a) there is a high prevalence of "sedentary" and "very sedentary" children and adolescents; b) boys present a higher PAL than girls; c) adolescents are less active than children, and d) the number of hTV is high in the group studied.